FEE IJARAH DALAM PRODUK PEMBIAYAAN TALANGAN HAJI (Analisis Penerapan Fatwa DSN-MUI No. 29 Tahun. 2002 di Bank Syariah Cabang Semarang) - Ajib, Ghufron (Economica: Jurnal Ekonomi Islam, 2013)
Qualitative issue discussed in this study is: "how is consistency ijarah fee in product  financing arrangement Hajj bailout at Syariah Bank in relation to the provision of normative ijarah fee in the DSN-MUI Fatwa No. 29 Th. 2002 and what main factor hindered the implementation of the fatwa. Data about the Arrangement of the Hajj bailout financing obtained from three Islamic banks Semarang branch through two methods of documentation and interviews. Study on substance DSN 29 of 2002, actually offering two models in the arrangement  of the Hajj bailout funding: through qardh or through ijarah contract. There is no indication that the Fatwa  requires the merger two  agreement contract. Ijarah contract made by the BPS and its customers over the filing and registration services to SISKOHAT to get a seat portion of Hajj is ijarah practices that do not conform to the requirements of the contract of ijarah. Because of the service and the work performed by the bank is already a BPS duties. Ijarah fee levied by Bank Muamalat Indoneisa (BMI) in the financing pattern Bailout Hajj, though not violate the provisions of the  DSN fatwa, but does not meet the requirements of ijarah contract as provided in Islamic law (fiqh). The Ijarah fee levied by Bank Syariah Mandiri (BSM) and BNI Shariah, not in accordance with the fatwa DSN, as calculated by the nominal amount of the bailout and the the contract period. Misconceptions in understanding the content of this fatwa is caused due to lack of a comprehensive understanding of the elements contained in the fatwa.